Augustus Hamilton : appropriation, ownership and authority : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University - Pishief, Elizabeth (Massey University, 1998)
Augustus Hamilton (1853 - 1913) was a scientist and ethnologist whose appointment to the position of Director of the Colonial Museum in 1903 was politically motivated. This thesis examines the interrelationship between the appropriation of taonga Maori, the concept of ownership and the assumption of the authority to manage Maori heritage within the colonial context. The life of Augustus Hamilton provides a case study to explore the themes of colonial appropriation and national identity. The study also provides essential background for a number of important contemporary issues. The purpose of the thesis is to connect four episodes in Hamilton's life to demonstrate a consistent development in his interest in the preservation of Maori heritage within the colonial context. The philosophical and academic movements in the nineteenth century which contributed to Hamilton's intellectual and professional development are discussed before exploring the early years of his career in Hawke's Bay when he established his reputation as a collector, gained his museum skills and built up a network of people interested in science and ethnology. Then the role he played in pressing for legislation to control the export of Maori art and its corollary the establishment of a national Maori museum is examined before demonstrating how his expertise and contacts enabled him assist the Government in the establishment of a politically motivated collection of Maori ethnology and the impact his philosophy has had on New Zealanders' perception of Maori culture until the present time. Finally I wish to thank my four children Justin, Kate, Alexander and Evelyn and my parents for their support and understanding over the years while I have endeavoured to complete this thesis.
Keywords: Augustus Hamilton; New Zealand. Maori Antiquities Act 1901; Dominion Museum; Ethnologists, New Zealand; Museums, New Zealand; Maori antiquities; Ethnic attitudes